FORMULATION AND PHYSICAL QUALITY TESTS HAIR FERTILIZER PREPARATIONS FROM LEMONGRASS (Chrysopogon zizanioides L.) AND VCO (VIRGIN COCONUT OIL) - Junia Fitri Hayani; Gabena Indrayani Dalimunthe; Minda Sari Lubis; Rapita Yuniarti (FORTE JOURNAL, 2024)
Hair loss is the shedding of hair from the skin. The factor that causes hair loss is a lack of nutrition for hair growth. Pure coconut oil (VCO) and citronella oil contain saturated fatty acids with short and medium chains of carbon atoms, especially octanoic acid and decanoic acid and essential oils which can be used to nourish hair. The aim of this research is to determine the effectiveness of the combination of citronella oil and VCO oil as a hair-fertilizing oil. This research was carried out using experimental methods including collecting and identifying samples, evaluating oil preparations, then testing hair-fertilizing oil preparations on 3 rabbits which were divided into 6 groups, namely positive control, negative control, formula 1, formula 2, formula 3 and formula 4. Data on the percentage of hair growth length were analyzed using the ANOVA (Analysis of Variance) method using the SPSS (Statistical Program for the Social Sciences) program. The results of the preparation evaluation showed that the oil preparation was stable during storage. The results showed that hair growth on day 28 with the positive control was 8.3 mm, negative control 4.17 mm, F1 4.83 mm, F2 5.17 mm, F3 6.33 mm and F4 7.83 mm. Duncan's test on day 28 showed that the positive control was not significantly different from formula 4, but was significantly different from formula 1, formula 2 and formula 3.